Modelling of ultrasonic wave propagation for industrial sonoreactor design and optimisation - Chu, Jin Kiat (2023)
The development of power ultrasound technology had raised interest in the design of sonoreactors. Numerical simulations were identified as a promising tool for tackling the challenges involved in scaling up and optimisation. The development of simulation strategies for sonoreactor acoustics had mainly focused on horn-type configurations, and little information was available for bath-type systems. This work evaluated the performance of three popular frequency-domain models for the prediction of acoustic pressure in bath-type configurations. The results of the pure-liquid, linear Commander and Prosperetti (CP), and nonlinear Helmholtz (NH) models were verified against hydrophone measurements and antinode characterisation results obtained from experiments. Emphasis was placed on the evaluation of the linear CP model, as it was hypothesised to best characterise the acoustic behaviour of the studied systems. In accordance with the objectives of this work, seven case studies were carried out.